Report of the Working Group on National Action Plan for Operationalising Clean Development Mechanism (CDM) in India - Planning Commission (Planning Commission, 2003)
The Convention allows Annex I Parties to implement policies and measures jointly with other Parties to help them return their emissions to 1990 levels. This clause underpinned the decision, at COP-1, to launch a pilot phase of so-called "Activities Implemented Jointly"(ALJ). Under AD, an Annex-I Party may implement a project that reduces emissions (e.g. energy conservation) or increase the removal of greenhouse gases by carbon sinks (e.g. reforestation) in the territory of another Party, including a developing country, but without gaining credit for the resulting emission reductions or removals.
Planning Commission Government of India
Planning Commission Government of India